Analisis Isi Teknik Propaganda Pada Pemberitaan Pembangunan Indonesia Di Majalah Tempo - Sulthan Jiyad Muqsith Asmara; Basril Basyar (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This research is motivated by the development of mass media which is growing day by day to shift the purpose of the media which was originally intended to convey information, educate, entertain and social control. The mass media were eventually used to launch propaganda using certain techniques to influence attitudes and behavior towards a certain person or group - in this case the news on Indonesia's development in Tempo Magazine. The research method that the author uses is a mix method with a content analysis model, the researcher focuses on how the physical unit, syntactic unit, referential unit, propositional unit and thematic unit, along with the influence of propaganda techniques on the coverage of Indonesian Development in Tempo Magazine. Total sampling and purposive sampling are sampling techniques used. This study found that all propaganda techniques appeared in the news on Indonesia's development in Tempo Magazine. Card Stacking and name calling are the most frequently used and rarely used techniques. This study also found that Card Stacking became the technique with the most physical units. Analysis of the syntactic unit, further together with the referential unit, found that Government Governance was the pillar using a lot of propaganda techniques. While the pillars of science and technology development mostly contain propaganda techniques in a propositional and thematic manner. Propaganda techniques that appeared in Tempo Magazine also brought changes to the reader's cognitive, affective, and psychomotor aspects.